FLEXICURITY STRATEGY IMPLEMENTATION IN THE LITHUANIAN LABOUR MARKET: THE ROLE OF POLITICAL PARTIES’ IDEOLOGY - PECIUKONYTĖ, LAURA (Politologija, 2012)
The concept of flexicurity is based on the idea that two goals – more flexibility and more security – in the labour market are not contradictory but mutually supportive and can be implemented simultaneously. It is also promoted by the EU as a solution for coping with various challenges labour markets face. The official EU documents (the main is Lisbon Strategy50) state that in order to remain competitive, reduce segmentation and combat the high unemployment level, the Member states have to implement the flexicurity strategy in four spheres. First, more flexible and reliable contractual arrangements have to be guaranteed. Second, comprehensive lifelong learning strategies should be developed in order to ensure the adaptability and employability of workers. Third, effective active labour market policies that help people to cope with transitions to new jobs have to be implemented. Fourth, modern social security systems that provide adequate income support, encourage employment, and facilitate labour market mobility must be assured. The object of this article is the implementation of the Flexicurity Strategy on the Lithuanian labour market. The aim of this study was to analyse the EU impact on Lithuania’s national employment policy in the area of flexicurity and the role of political parties’ ideology in this process. In order to achieve the goal, the concept of flexicurity and its evaluation model were introduced. Then the Europeanization theoretical approach and main factors influencing the of the EU impact on national policies were overviewed. Finally, a piece of the input–process–output model was used to quantify the implementation of the Flexicurity Strategy in Lithuanian labour market. Also, an analysis of legislative initiatives in the Parliament was conducted. It helped to evaluate whether the ideology of ruling parties influenced the content of the law initiatives (in the flexicurity area). The main findings of this article are as follows: – the EU impact on national employment policy in the area of flexicurity was minimal despite the favourable attitude of political parties towards the EU. The analysis of various indicators revealed that the biggest change happened in the input stage of flexicurity and all trials were about the promotion of the functional and numerical aspects of flexibility. As regards the other dimensions and levels, the situation mostly remained status quo; – political parties in the government were quite active in proposing various bills connected with flexicurity. However, only about half of them reflected the EU attitude to flexicurity. Also, employment policy reform measures were chosen selectively, and flexicurity as a strategy was not implemented. One of the reasons was a high selectivity of implemented measures and the lack of approach to flexicurity as a strategy. It could be changed by starting to initiate public debates and discussions about the principle of flexicurity (until now, no public debates on this topic have been organized in the country). This could help to increase public awareness, deepen understanding and to find an appropriate solution; – the left wing government was more active in implementing the income security dimension in the labour market. Most of the accepted decisions contradicted the EU attitude to how security should be promoted: they were connected with a more active use of passive labour market policies. Meanwhile, the right-wing government was more active in promoting flexibility in the labour market. Also, it accepted more “EU-friendly” laws. This confirmed the statement that the ideology of the ruling parties has an explanatory impact while choosing and initiating legislative proposals on flexicurity. However, this statement requires further research, because during the analysis it was impossible to limit the impact of the economic crisis on legislative initiatives. An additional analysis revealed that this factor had also an impact on adopting laws related to the labour market flexibility.